A two-phase modeling strategy for analyzing the failure process of masonry arches. (1st June 2020) - Zhao, Chao; Xiong, Yunlong; Zhong, Xingu; Shi, Zheng; Yang, Sheng
Highlights: A two-phase modeling strategy is proposed to consider the anisotropy of masonry materials. Stone blocks and mortar joints are modeled individually by introducing cohesive elements. The compression-shear behavior of masonry materials is tested and considered in the numerical modeling. The modeling strategy is validated against the results from the tested arch. Influence of friction coefficients and load positions on the failure behavior of masonry arches is discussed. Abstract: The anisotropy and meso-structure of masonry materials bring great difficulty for the numerical modeling of masonry arch bridges. To overcome this problem, a two-phase numerical modeling strategy based on cohesive elements is proposed and used to analyze the failure process of masonry arches in this study. According to the proposed strategy, masonry is assumed to be a two-phase material, which consists of two important components: stone blocks and mortar joints. Stone blocks are represented by solid elements where the compression failure is considered by introducing a nonlinear constitutive model. Mortar joints are described by zero-thickness cohesive elements, which are inserted into the interfaces of adjacent stone blocks automatically by a user-defined program. A Mohr-Coulomb type constitutive model supported by experimental results is proposed to describe the mechanical behavior of mortar joints, and two failure modes (tension and shear failure) are considered. The effectiveness of the proposed strategy is firstly identified by comparing with the experimental results, and then a sensitivity analysis is conducted to investigate the influence of the friction coefficients and load positions on failure behavior of the masonry arch.